Gambaran Radiografi Toraks Pasien HIV Dengan Tuberkulosis Paru Berdasarkan Nilai CD4 Di Rumah Sakit Umum Arifin Achmad Provinsi Riau - Jendriella Jendriella; Dian Yazmiati; Andreas Makmur; Azizman Saad (Jurnal Ilmu Kedokteran, 2019)
Diagnosis of tuberculosis in HIV-Tuberculosis coinfected patients is difficult. Thorax x-ray is a primary tool to evaluate tuberculosis in HIV. The purpose of this cross-sectional study was to assess and compare various radiological patterns of pulmonary tuberculosis in HIV patients with CD4 counts. This study conducted in Arifin Achmad Hospital Riau province from December 2016-December 2018 with 55 HIV-tuberculosis coinfected patients. WHO guidelines were used for diagnosis of HIV and tuberculosis. 100% of the patients had sputum positive pulmonary tuberculosis, with higher incidence (83,6%) among CD4 less than 200 as compared to CD4 more than 200 (16,4%). Infiltration (32,7%) followed by normal (18,2%), and fibrosis (11%) seen with CD4 less than 200. Infiltration (9,2%) followed by normal(3,6%) and fibrosis (1,8%) with CD4 above 200. Mid and lower zone (50%) more commonly seen in CD4 < 200. Despite in CD4 >200 upper zones more commonly seen. Most lesions were found in mid zone of lung. There were significant differences in radiological patterns of pulmonary tuberculosis in HIV according to CD4 counts.